Investigating the occurrence of Kelvin-Helmholtz instabilities at Jupiter’s dawn magnetopause - Montgomery,J; Ebert,R; Allegrini,F; Bagenal,F; Bolton,S; DiBraccio,G; Fuselier,S; Wilson,R; Masters,A (Geophysical Research Letters, 2023)
We use the Kelvin-Helmholtz instability (KHI) condition with particle and magnetic field observations from Jovian Auroral Distributions Experiment and MAG on Juno along the dawn flank of Jupiter's magnetosphere. We identify the occurrence of magnetopause crossings that show evidence of being KH (Kelvin-Helmholtz) unstable. When estimating the k vector to be parallel to the velocity shear, we find that 25 of 62 (40%) magnetopause crossings satisfy the KHI condition. When considering the k vector of the maximum growth rate through a solid angle approach, we find that 60 of 62 (97%) events are KH unstable. This study shows evidence of KH waves at Jupiter's dawn flank, including primary drivers such as high velocity shears and changes in plasma pressure. Signatures of magnetic reconnection were also observed in ∼25% of the KH unstable crossings. We discuss these results and their implication for the prevalence of KHI at Juno's dawn magnetopause as measured by Juno.